Thickness Measurement of V2O5 Nanometric Thin Films Using a Portable XRF. (24th January 2016) - Lopes, Fabio; Cardozo Amorin, Luís Henrique; da Silva Martins, Larissa; Urbano, Alexandre; Roberto Appoloni, Carlos; Cesareo, Roberto
Abstract : Nanometric thin films have always been chiefly used for decoration; however they are now being widely used as the basis of high technology. Among the various physical qualities that characterize them, the thickness strongly influences their properties. Thus, a new procedure is hereby proposed and developed for determining the thickness of V2 O5 nanometric thin films deposited on the glass surface using Portable X-Ray Fluorescence (PXRF) equipment and the attenuation of the radiation intensity K α of calcium present in the glass. It is shown through the present paper that the radiation intensity of calcium K α rays is proportional to film thickness in nanometric films of vanadium deposited on the glass surface.